Green Economy Integration for Sustainable BUMDES: A Case Study of Kintamani, Bali - Septien Dwi Savandha; Amelia Amelia (Journal of Economic Development and Village Building, 2025)
One of the strategies to attain local sustainable development is integrating green economy principles into rural economic enterprises. Using a qualitative case study approach, this research explores how green economy is integrated into rural economic enterprises in the Kintamani District, Bali. Data collection was carried out by conducting in-depth semi-structured interviews with 22 stakeholders and observing the area under study. The data obtained were analyzed using thematic analysis. Results of the research point to the following: 78% of the managers of BUMDES claimed that the main obstacle was the lack of initial capital, while 85% of all interviewees mentioned an existing institutional gap. Yet, 92% of the respondents assessed the economic potential of green models as positive in the long run. On the contrary, 75% of young people and those with higher education greeted the change, while only 45% of farmers with over 20 years of experience showed a willingness for change. The study proposes a four-stage roadmap comprising establishment, piloting, expansion, and institutionalization. Results indicate that the gradual approach received 95% support from stakeholders, and when accompanied by training, the percentage of adoption can be increased by 68% in pilot projects. The study concludes that the transformation to a green economy is an inevitable necessity for ensuring the long-term well-being of the community and protection of the natural and cultural assets of the Kintamani BUMDES.